Developing of rural settlement landscape gene research system based on content analysis - Hua Xu; Tianhang Zhang; Beichen Ge; Yuhong Song (Journal of Asian Architecture and Building Engineering)
Based on the issue of how to preserve vernacular landscape characters in the process of rural development, an innovative research system for identifying the extrinsic characters and the intrinsic value of village landscapes was developed through content analysis. Landscape genes are values, knowledge, cultural practices, and modes of thought implicit in the rural landscapes. The village landscape gene research system includes three aspects: landscape element and trait research, landscape composition regularity research, and landscape genes research; as well as two stages: extracting landscape genes and exploring the adaptability of landscape genes. Afterwards, through the content extraction and statistical analysis of 182 theses, 71 descriptive indices for landscape gene research were selected from the scales of rural environment, internal space of the village and vernacular architecture respectively. A comparative map of the landscape element traits and composition regularities of the two traditional villages, Wuli village and Baya Middle village, was drawn based on the index system. The research framework developed in this study has great significance for recommending rural development and management policies as well as enhancing the identification and belonging of local communities, especially for ethnic minority people.